Enhancing clinical complete response assessment in rectal cancer: integrating transanal multipoint full-layer puncture biopsy criteria: a systematic review - Liu, Xin; Duan, Boshi; Liu, Ruibin; Zhu, Mengying; Zhao, Guohua; Guan, Ning; Wang, Yue (Frontiers in Oncology, 2024)
There is currently a lack of standardized criteria for evaluating clinical complete response (cCR) in rectal cancer post-neoadjuvant chemoradiotherapy (nCRT), often resulting in discrepancies with true pathological complete response (pCR). Staging local lesions via MRI is challenged by tissue edema and fibrosis post-nCRT, while endoscopic biopsy accuracy is compromised by residual cancer foci in the muscular layer. Transanal local excision offers a relatively accurate assessment of lesion regression but poses challenges including impaired anal function and elevated complication rates. Building on current diagnostic frameworks, we propose enhancing cCR assessment by integrating histological criteria from transanal multipoint full-layer puncture biopsy (TMFP). This approach aims to improve accuracy while minimizing complications, offering promise for patients opting for observation-based treatments. Further research is needed for definitive conclusions.